2021
DOI: 10.3389/fpsyg.2021.764081
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Teaching Performance in Psychology: Invariance According to Age, Sex, and Academic Stage of Peruvian Students

Abstract: The use of scales to assess the performance of professors from the students' standpoint is a generalized practice in higher education systems worldwide. The purpose of this study is to analyze the factorial structure and measure the invariance of the Scale of Teaching Performance of the Psychology Professor (EDDPsic) among groups according to gender, age, and academic stage. The sample of participants was composed of 316 Psychology students from the fourth and sixth semesters (basic cycles), and from the eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
(132 reference statements)
0
12
0
1
Order By: Relevance
“…Self-reports derived from this model of didactic performance have achieved stability and construct validity with restricted models of both teacher and student, and of various disciplines, contexts and educational levels [7,29,41]. Likewise, good goodness-of-fit has been found in predictive structural regression models with structural equation modeling.…”
Section: The Conceptual Framework Of This Studymentioning
confidence: 76%
“…Self-reports derived from this model of didactic performance have achieved stability and construct validity with restricted models of both teacher and student, and of various disciplines, contexts and educational levels [7,29,41]. Likewise, good goodness-of-fit has been found in predictive structural regression models with structural equation modeling.…”
Section: The Conceptual Framework Of This Studymentioning
confidence: 76%
“…OECD, 2017). According to the PISA tests, three general dimensions have been identified in the case of teaching practice behaviors: 1. teacher-led instruction: teacher behaviors for class structuring, defining objectives, monitoring the progress of the students, and modeling the skills to be developed by the latter; 2. formative assessment: behaviors of progressive feedback to their students, providing information about their weaknesses and strengths, fostering reflection on their expectations, goals, and progress throughout the learning process; 3. student orientation: behaviors of the teacher focused on the traits and needs of each student to advance through the contents and guarantee the acquisition of knowledge (Bazán-Ramírez et al, 2021b).…”
Section: Teaching and Feedback In The Students' Learningmentioning
confidence: 99%
“…The teaching factor included two latent variables of teacher performance: explicitness and illustration, and the feedback factor included three latent variables of teacher performance: supervision of learning activities, feedback, and evaluation. These five criteria of teacher performance stem from the didactic performance model in the context of the teaching of psychology and related disciplines (Carpio, et al, 1998;Irigoyen et al, 2011;Silva, et al, 2014;Velarde and Bazán, 2019;Bazán-Ramírez et al, 2021b). Also, this model included four latent student performance variables as correspondence with the didactic performance variables of the teacher: St evaluation-application, St illustration-participation (which is functionally related to the teaching factor of teacher performance), St practice, and St feedback-improvement (which are functionally related to the feedback factor of teacher performance).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the literature revealed that there are few studies that investigate the MI in the SET using different grouping methods. Bazán-Ramírez et al (2021) tested the MI of the teaching performance of the psychology professor scale according to gender, age, and academic stage using the MGCFA, and the measurement noninvariance was found on the grouping factors. Kalender and Berberoğlu (2019) assessed the MI of student rating of instruction between high and low-achieving classrooms.…”
Section: Introductionmentioning
confidence: 99%